Learning the History of Islamic Culture as a Medium for Cultivating Character Education at IRA Medan Middle School - Bunga Sari Siagian; Muhammad Basri (Yayasan Azhar Amanaa Yogyakarta, 2026)
The crisis of moral degradation among adolescents is a key phenomenon underpinning the importance of strengthening student character. This study aims to analyze the role of Islamic Cultural History learning, identify character values, describe obstacles, and formulate recommendations at IRA Medan Junior High School. The method used was descriptive qualitative through observation, in-depth interviews, and documentation of teachers and students. The findings indicate that Islamic Cultural History learning plays a significant role in instilling the values of discipline, honesty, responsibility, and patience through exemplary figures and storytelling methods. This study's contribution demonstrates positive behavioral changes in students at school and at home. However, limitations in internalizing values lie in differences in student readiness, limited time allocation, and a less than conducive external social environment. Consequently, individual coaching by teachers has not been optimal. Recommendations call for strong synergy between schools, families, and the community, along with the development of innovative, more contextual learning methods.